A moose that says moo - Hamburg, Jennifer; Truesdell, Sue (New York : Farrar Straus Giroux, 2013)
"Chaos ensues when a child imagines a zoo filled with animals doing the unusual and the unlikely"--
Keywords: Stories in rhyme; Zoos -- Fiction; Zoo animals -- Fiction; Animals -- Fiction; Humorous fiction